2012
DOI: 10.1080/00087114.2012.752920
|View full text |Cite
|
Sign up to set email alerts
|

Cytological studies onPrimulinataxa (Gesneriaceae) from limestone karsts in Guangxi province, China

Abstract: Primulina, a large genus restricted mainly to limestone karst areas, was chosen as a suitable subject for the study of speciation patterns in its center of diversity and endemism at the chromosomal level. We investigated the chromosome numbers and chromosome morphology for 39 species, three varieties and 11 undescribed taxa of Primulina collected from limestone karsts in Guangxi province, China, half of which are known so far to be endemics. The chromosome numbers for the taxa examined were found to be highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
6
1
Order By: Relevance
“…S2), which is consistent with that reported by Liu et al . (), but different from the report of Christie et al . (), suggesting intraspecific variation of ploidy levels in the species.…”
Section: Resultscontrasting
confidence: 96%
See 2 more Smart Citations
“…S2), which is consistent with that reported by Liu et al . (), but different from the report of Christie et al . (), suggesting intraspecific variation of ploidy levels in the species.…”
Section: Resultscontrasting
confidence: 96%
“…(), suggesting intraspecific variation of ploidy levels in the species. Our results confirmed that chromosome numbers in Primulina are uniform, as reported before (Christie et al ., ; Liu et al ., ). The flow cytometry analysis yielded high‐resolution histograms with coefficient of variance (CV) < 5% for the majority of measurements (Table S1).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Chromosomes of Primulina have been studied, measured and found to be small in size according to the classification of Lima‐de‐faria (), within the range 0.6–2.4 μm (Liu et al ). The somatic chromosomes of P. melanofilamenta at metaphase are illustrated in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Although the new generic circumscription reflects better the evolutionary relationships and ecological preferences of the genus, diagnostic characters of Primulina , such as perennial habit and acaulescent rosette (2011) and the basic chromosome number, x = 18 (Christie et al 2012; Liu et al 2012), are not exclusive to the genus. The lack of strong morphological synapomorphies to distinguish it from related genera in the region necessitates molecular data in ascertaining generic placements (Xu et al 2012ab).…”
Section: Introductionmentioning
confidence: 99%